Concepts for the Development of Person-Centered, Digitally Enabled, Artificial Intelligence–Assisted ARIA Care Pathways (ARIA 2024) - Bousquet, Jean (2024)
Funding Information: This work has received funding from ARIA (Allergic Rhinitis and its Impact of Asthma); CATALYSE (Climate Action To Advance HeaLthY Societies in Europe), the European Union\u2019s Horizon Europe research and innovation program under grant agreement no. 101057131; FRAUNHOFER Institute for Translational Medicine and Pharmacology (ITMP), Immunology and Allergology, Berlin, Germany; University of Porto, Portugal; and MASK-air, which has been supported by EU grants (Impact of air Pollution on Asthma and Rhinitis [POLLAR] project of the European Institute of Innovation and Technology Health; Structural and Development Funds, R\u00E9gion Languedoc Roussillon and Provence-Alpes-C\u00F4te d\u2019Azur; Twinning, European Innovation Partnership on Active and Healthy Ageing, DG Sant\u00E9 and DG Connect); educational grants from Mylan-Viatris, Allergologisk Laboratorium K\u00F8benhavn, GlaxoSmithKline, Novartis, Stallerg\u00E8nes-Greer, and Noucor; and funding from Breathing Together Onlus Association (Associazione Respiriamo Insieme Onlus), Italy; Esp\u00EDritu Santo University, Samborond\u00F3n, Ecuador; Finnish Anti-Tuberculosis Association Foundation and Tampere Tuberculosis Foundation; GA 2 LEN; German Allergy Society AeDA (\u00C4rzteverband Deutscher Allergologen); IPOKRaTES (International Postgraduate Organization for Knowledge transfer, Research and Teaching Excellent Students) Lithuania Fund; Polish Society of Allergology (POLSKIE TOWARZYSTWO ALLERGOLOGICZNE); and University of Li\u00E8ge, Belgium. Funding Information: Conflicts of interest: J. Bousquet reports personal fees from Cipla, Menarini, Mylan, Novartis, Purina, Sanofi-Aventis, Teva, Noucor, other from KYomed-Innov, and other from Mask-air-SAS, outside the submitted work. M. Blaiss reports personal fees from Sanofi, personal fees from Regeneron, personal fees from ALK, personal fees from Merck, personal fees from AstraZeneca, personal fees from GSK, personal fees from Prollergy, personal fees from Lanier Biotherapeutics, and nonfinancial support from Bryn Phama, outside the submitted work. J. Lity\u0144ska reports personal fees from Evidence Prime Sp. z o.o., outside the submitted work. T. Iinuma reports grants from Sanofi, outside the submitted work. P. Tantilipikorn reports grants from Abbott, other from GSK, and other from Sanofi Aventis, outside the submitted work. T. Haahtela reports personal fees from Orion Pharma, outside the submitted work. Publisher Copyright: © 2024 The Authors